A Study to Assess the Level of Living and Awareness and Practices Regarding MCH Care in A Remote Tribal Village of Udaipur District - Kumar, Arun; Sharma, Shalabh; Sharma, Chandra Prakash; Meghwal, Suresh Chandra (National Journal of Community Medicine, 2013)
Introduction: Cultural patterns, lifestyle and health seeking behavior of tribal population observed to vary a lot in previous studies. Health awareness and the level of living observed to be poor among tribal people. Objective: Present study was done in order to assess the level of living with emphasis on awareness and prevalent practices regarding Maternal and Child Health care among the tribal population of a remote village. Methodology: A family based community health survey was done in a tribal village Bakhel of Udaipur. Data collected by observation on a pre designed and pre structured interview schedule of mostly female heads of all the families consented. Results: Only 20% of male heads are literate and female literacy much lower, 60 s% families preferred to deliver at home, 62% of families had no knowledge about child immunization, 61% of children found to have some grade of malnutrition. Conclusion: Most of the tribal villagers are Illiterate; have poor awareness regarding availability of MCH services, routine immunization and family planning methods.